Impact of Foreign Direct Investment on the Carbon Dioxide Emissions of East Asian Countries Based on a Panel ARDL Method - Wang, Yuan; Huang, Yingjun (Frontiers in Environmental Science, 2022)
The problem of air pollution caused by carbon dioxide emissions has gradually attracted the international community's attention. The study shows the effect of foreign direct investment on carbon dioxide emissions in East Asia. Based on the 2011–2020 panel data of East Asian countries, the long- and short-term impacts of trade, foreign direct investment (FDI), and economic growth on the carbon dioxide (CO2) emissions of these nations are estimated using an autoregressive distributed lag model. The results show that in the short term, an increase in per capita gross domestic product (GDP) in the current and previous periods will increase carbon dioxide emissions; an increase in FDI in the current and previous periods will increase CO2 emissions; an increase in trade openness in the current period will increase CO2 emissions. In the long term, per capita GDP, FDI, and trade openness have no significant impact on CO2 emissions. We should encourage foreign-invested enterprises to use and disseminate clean production technologies and environmentally friendly management methods and pay attention to trade structure adjustment.